Examination of correlation between lead and histidine in Eleagnus angustifolia L., Vitis vinifera L., and Nerium oleander L using ICP-MS and HPLC-MS - Ozen, Sukran Akkus; Yaman, Mehmet (Perkin - Elmer Corp., 2016)
In this study, ICP-MS and HPLC-MS methods were used for the determination of lead and histidine, respectively, in the leaves of the plant species Eleagnus angustifolia L., Vitis vinifera L. and Nerium oleander L., sampled at industrial areas, including the cities of Gaziantep and Bursa, Turkey. In the determination of histidine by HPLC-MS, all of the system parameters such as flow rate of the mobile phase, fragmentation potential, injection volume and column temperature were optimized and found to be 0.2 mL min-1 70 V, 15 ?L and 20 °C, respectively. Histidine was extracted from the plant sample by ultrapure water at 90 °C for 30 minutes. The concentrations of histidine were found to be in the range of 3-23 mg kg-1 for Eleagnus angustifolia L., 2-33 mg kg-1 for Vitis inifera L., and 3-11 mg kg-1 for Nerium oleander L. The concentrations of Pb were in the range of 1-45 mg kg-1 for Eleagnus angustifolia L., 1-32 mg kg-1 for Vitis vinifera L. and 1-53 mg kg-1 for Nerium oleander L. A linear correlation between Pb and histidine for Eleagnus angustifolia L. at r=0.77 was found.